find the value of a if (x-a) is a factor of
![{x}^{5} - {a}^{2} {x}^{3} + 2x + a + 3 {x}^{5} - {a}^{2} {x}^{3} + 2x + a + 3](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B5%7D++++-++%7Ba%7D%5E%7B2%7D++%7Bx%7D%5E%7B3%7D++%2B+2x+%2B+a+%2B+3)
hence factorise
![{x}^{2} - 2ax - 3 {x}^{2} - 2ax - 3](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B2%7D++-+2ax+-+3)
Answers
Answered by
15
Hello,.
Let
![p(x) = {x}^{5} - {a}^{2} {x}^{3} + 2x + a + 3 p(x) = {x}^{5} - {a}^{2} {x}^{3} + 2x + a + 3](https://tex.z-dn.net/?f=p%28x%29+%3D++%7Bx%7D%5E%7B5%7D++-++%7Ba%7D%5E%7B2%7D++%7Bx%7D%5E%7B3%7D++%2B+2x+%2B+a+%2B+3)
Given that (x-a) is a factor of p(x).
So,
By the factor theorem
X-a =0
Or, x = a
Now putting x=a in p(x)
So,
Again by factor theorem
...
P(a) =0
So,
![{x}^{5} - {a}^{2} {x}^{3} + 2x + a + 3 \\ = {a}^{5} - {a}^{2} {a}^{3 } + 2a + a + 3 \\ {a}^{5} - {a}^{5} + 3a + 3 = 0 \\ 3a + 3 = 0 \\ 3a = ( - 3) \\ a = \frac{( - 3)}{3} = ( - 1) {x}^{5} - {a}^{2} {x}^{3} + 2x + a + 3 \\ = {a}^{5} - {a}^{2} {a}^{3 } + 2a + a + 3 \\ {a}^{5} - {a}^{5} + 3a + 3 = 0 \\ 3a + 3 = 0 \\ 3a = ( - 3) \\ a = \frac{( - 3)}{3} = ( - 1)](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B5%7D++-++%7Ba%7D%5E%7B2%7D++%7Bx%7D%5E%7B3%7D++%2B+2x+%2B+a+%2B+3+%5C%5C++%3D++%7Ba%7D%5E%7B5%7D++-++%7Ba%7D%5E%7B2%7D++%7Ba%7D%5E%7B3+%7D++%2B+2a+%2B+a+%2B+3+%5C%5C+++%7Ba%7D%5E%7B5%7D++-++%7Ba%7D%5E%7B5%7D++%2B+3a+%2B+3+%3D+0+%5C%5C+3a+%2B+3+%3D+0+%5C%5C+3a+%3D+%28+-+3%29+%5C%5C+a+%3D++%5Cfrac%7B%28+-+3%29%7D%7B3%7D++%3D+%28+-+1%29)
We got the value of a as (-1)
Now ,
Putting this in other polynomial...
x² - 2(-1)x - 3
Or
x² + 2x - 3
By middle term splitting, we are factorising the polynomial
So,
x² +3x - x - 3
Or, x(x+3) - 1(x+3)
Or, (x+3)(x-1)
Hope this will be helping you ✌️
Let
Given that (x-a) is a factor of p(x).
So,
By the factor theorem
X-a =0
Or, x = a
Now putting x=a in p(x)
So,
Again by factor theorem
...
P(a) =0
So,
We got the value of a as (-1)
Now ,
Putting this in other polynomial...
x² - 2(-1)x - 3
Or
x² + 2x - 3
By middle term splitting, we are factorising the polynomial
So,
x² +3x - x - 3
Or, x(x+3) - 1(x+3)
Or, (x+3)(x-1)
Hope this will be helping you ✌️
Similar questions